Trabalhadoras do Care na Saúde Mental: Contribuições marxianas para a profissionalização do cuidado feminino - Passos, Rachel Gouveia (2016)
The thesis presented seeks to propose a care approach based the theoretical foundations of Marxism, objectifying to contribute to the professionalization of this work. Changes in the world of work, caused by the productive restructuring and by neoliberalism, from the 1970s, provoked new settings on the social and sexual division of labor, both in the productive sphere and in reproductive. The participation of women in the productive sphere occurred in a contradictory manner, since it was marked by precariousness, the labor flexibilization, outsourcing contract and particularly in jobs in the service sector. With the globalization of the commodification of welfare, new occupations have emerged and allowed the inclusion of many women in the formal and informal labor market. Given this reality, the feminine care suffered its commodification and has been internationally demanded as work. Our research aims to identify the new settings that require the professionalization of feminine care in the contemporary international scene, seeking to differentiate housework care work, from the theories of care, and to propose a new approach to this category, based at historical and dialectical materialism. Regarding field research we highlight the caregivers who work in mental health policy, more specifically those working in residential care homes in the municipality of Rio de Janeiro and also two courses that were offered to this audience in the Polytechnic Health School Joaquim Venancio in the Oswaldo Cruz Foundation. The survey results allow us to state that this work is performed mostly by black women, belonging to the impoverished sections of society, which enables us to demonstrate that invisibility and subordination of professions, occupations and functions carried out by women are still permeated by inequalities / class oppressions, gender and race / ethnicity, and are linked to a essentialization and naturalization said female standards. All this directly implies not professionalisation and recognition of this type of work